Recent Advancements of Embedded System in HMI - Darney, P. Ebby (IRO Journal on Sustainable Wireless Systems, 2024)
Human-Machine Interaction (HMI) refers to the interface and interaction between humans and machines, often in the context of technology-driven systems. In the realm of vehicular systems, HMI plays a crucial role in facilitating communication between drivers, passengers, and the vehicle itself. The driving experience is completely transformed by the quick developments in embedded systems, with the Human-Machine Interface (HMI) having a major influence on how drivers and cars interact. This study examines the most current developments in HMI design and execution, emphasizing how they have improved the usability, safety, and intuitiveness of vehicle operation interfaces.
Keywords: Touchscreens; Gesture Controls; Advanced Voice Commands; Augmented Reality Displays; And Head-Up Displays